La certificación de sostenibilidad turistica (CST): facilita la certificacion ISO 9000: el caso del HPL - Vasconcelos Vásquez, Kattia Lizzett (2011)
The value of this paper lies in the fact that it provides a comparative analysis between ISO 90001:2000 standards and the Costa Rica CST sustainability standard. It aims to obtain differences and similarities between both certification systems from this comparison and to analyze how they contribute to business management and sustainability. The analysis highlights which organizational changes a company must develop in order to achieve efficiency and ensure customer satisfaction.